EMERGENCY SITUATIONS RELATED TO EPIPHYTOTY: CHALLENGING ISSUES OF AGRICULTURAL PEST CONTROL AND MASS PLANT DEATH - B.Sodikov (Galaxy International Interdisciplinary Research Journal, 2023)
In all the irrigated regions of Central Asia, there are reports that bollworms cause considerable annual damage to pea, tomato, tobacco, and corn crops. According to estimates, the bollworm kills 0.5-1.5% of the total cotton crop in Central Asia. It can be seen that the damage caused by the bollworm pest naturally increases in years with many infestations (when the spring is warm after a warm winter).